A quasi-evolutionary identification attempt to modelling of steel frames - Paczkowski, Witold M.; Badower, Aleksander; Silicka, Ewa; Silicki, Adrian (Computer Assisted Methods in Engineering and Science, 2023)
The work presents a process of analytical identification via a standard steel frame example. Some experimental tests are made to verify the identification process. Under controlled external loadings the values of displacements and strains are recorded and an approximate FEM-based model is formulated. The polyoptimization approach is employed to analyze that model. The compatibility criteria for comparison of theoretical and experimental models are assumed as square sums of differences between displacements and strains. The whole problem is proceeded in three cycles of evolution suggested by the authors.